1987
DOI: 10.1136/bjo.71.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Congenital iris cysts.

Abstract: SUMMARY Unilateral, spontaneous, non-pigmented iris cysts appeared before the age of 2 years in four patients. Histopathological specimens obtained in three cases showed stratified to cuboidal, non-pigmented, epithelial lined cysts. Goblet cells were recognised in two of the three specimens. The clinical features and histopathological findings indicate that these cysts are derived from surface ectoderm and may be congenital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…156,176,177 Focal corneal oedema may arise as a result of contact between the stromal cyst and the corneal endothelium. 137,142,161,163 Raised intraocular pressure, 159,163,172,173 hyphaema 137 iritis, and subluxation of the lens 163,167,171,[173][174][175] have been found in association with primary iris stromal cysts.…”
Section: Iris Cystsmentioning
confidence: 99%
See 4 more Smart Citations
“…156,176,177 Focal corneal oedema may arise as a result of contact between the stromal cyst and the corneal endothelium. 137,142,161,163 Raised intraocular pressure, 159,163,172,173 hyphaema 137 iritis, and subluxation of the lens 163,167,171,[173][174][175] have been found in association with primary iris stromal cysts.…”
Section: Iris Cystsmentioning
confidence: 99%
“…170,180 Immunohistochemical studies have demonstrated a positive reaction for epithelial cytokeratin markers and a negative result for the S100 antigen. 159,163,166,170 Electron microscopic studies have shown the presence of microvilli on the luminal surface of the epithelial cells together with desmosomes and tonofilaments. 163,166,170,178 These studies support the notion that primary iris stromal cysts originate from the surface ectoderm, displaced probably at the time of formation of the lens vesicle.…”
Section: Iris Cystsmentioning
confidence: 99%
See 3 more Smart Citations